2018
DOI: 10.1111/ncn3.12232
|View full text |Cite
|
Sign up to set email alerts
|

Atypical type of familial Mediterranean fever: An underdiagnosed cause of chronic aseptic meningitis

Abstract: We report an atypical case of familial Mediterranean fever (FMF) concomitant with chronic aseptic meningitis. The patient experienced fever, abdominal and back pain because of serositis, and headache because of aseptic meningitis for 4 weeks. Blood examinations revealed increased white blood cells and serum amyloid A level. Medications, including steroids, did not improve his symptoms. However, the patient experienced immediate relief after the administration of colchicine. We diagnosed him as having atypical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Capton et al proposed diagnostic criteria for recurrent meningitis related to FMF, as follows: (a) Episodes of RAM due to FMF should be accompanied by other clinical or biological features of FMF attacks; (b) colchicine should prevent or lessen episodes; and (c) other classical causes of RAM should be excluded (9). In a systematic review investigating the association between FMF and RAM, there were only five confirmed cases of FMF and RAM (including the present case), although the differential diagnosis mentioned above was incomplete in three cases (10)(11)(12)(13) (Table). In previous case reports, the authors failed to sufficiently exclude or describe the exclusion of other diseases (11,13).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Capton et al proposed diagnostic criteria for recurrent meningitis related to FMF, as follows: (a) Episodes of RAM due to FMF should be accompanied by other clinical or biological features of FMF attacks; (b) colchicine should prevent or lessen episodes; and (c) other classical causes of RAM should be excluded (9). In a systematic review investigating the association between FMF and RAM, there were only five confirmed cases of FMF and RAM (including the present case), although the differential diagnosis mentioned above was incomplete in three cases (10)(11)(12)(13) (Table). In previous case reports, the authors failed to sufficiently exclude or describe the exclusion of other diseases (11,13).…”
Section: Discussionmentioning
confidence: 79%
“…In a systematic review investigating the association between FMF and RAM, there were only five confirmed cases of FMF and RAM (including the present case), although the differential diagnosis mentioned above was incomplete in three cases (10)(11)(12)(13) (Table). In previous case reports, the authors failed to sufficiently exclude or describe the exclusion of other diseases (11,13). Despite the relatively short observation period following colchicine treatment in the present case, our patient has experienced no recurrence to date.…”
Section: Discussionmentioning
confidence: 79%
“…However, in Japan, there are more patients with FMF, carrying heterozygous mutations in the MEFV gene than those carrying homozygous mutations [3]. In addition, in a limited number of cases with a heterozygous MEFV p.Ser503Cys exon 5 variant, the patients have been phenotypically diagnosed with atypical FMF (Table 2) [9][10][11]. It remains perplexing why patients with heterozygous MEFV p.Ser503Cys exon 5 variant present atypical FMF manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient had frequent complaints of headache, which is not included in the symptoms of FMF. We did not perform further evaluation of his cerebrospinal fluid; however, a study reported an atypical FMF patient with compound heterozygous mutations in exons 2 and 5 (E148Q/S503C) in MEFV who experienced recurrent headache due to chronic aseptic meningitis [ 9 ]. Although it is difficult to strongly suggest from such a small number of cases, it is possible that headache due to aseptic meningitis is one of the complications in atypical FMF, and atypical FMF could be a differential diagnosis in periodic fever patients with headaches.…”
Section: Discussionmentioning
confidence: 99%
“…Pubmed/MEDLINE was queried for "familial Mediterranean fever" and "aseptic meningitis". Articles involving patients with FMF suffering from aspetic meningitis, recurrent or single episode -were included 8,9,10,11,12 .…”
Section: Case Presentationmentioning
confidence: 99%